Electrocardiography Interpretation Competency of Medical Interns: Experience from Two Ethiopian Medical Schools - Melaku Getachew; Temesgen Beyene; Sofia Kebede (Emergency Medicine International)
Background. Electrocardiography (ECG) is the graphical display of electrical potential differences of an electric field originating in the heart. Interpretation of ECG is a core clinical skill in the department of emergency medicine. The main aim of this survey was to assess competency of ECG interpretation among 2018 graduating class medical students in Addis Ababa University and Haramaya University. Methodology. A cross-sectional survey was conducted on medical interns at Addis Ababa University and Haramaya University. Data had been collected from October 01, 2018, to October 30, 2018, by using structured questionnaires. Data were entered, cleaned, edited, and analyzed by using SPSS version 25.0 statistical software. Descriptive statistics, cross-tabs, chi-squared test, Mann–Whitney U test, and binary logistic regression were utilized. Results. Two-hundred and two graduating medical students were involved on this survey, out of which 61.3% (95% CI 56.3–66.3%) and 32.75% (95% CI 28.25–37.25) were able to correctly interpret the primary ECG parameters and the arrest rhythm of ECG abnormalities, respectively. The ability to detect from common emergency ECG abnormalities of anterioseptal ST segment elevation myocardial infraction, atrial fibrillation, and first-degree atrioventricular block was 42.6%, 39.1%, and 32.1%, respectively. Conclusion. This survey showed graduating medical students had low competency in ECG interpretations.